2012
DOI: 10.3758/s13415-012-0129-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of acute stress on Pavlovian-instrumental transfer in rats

Abstract: Pavlovian stimuli invigorate ongoing instrumental action, a phenomenon termed the Pavlovian-instrumental transfer (PIT) effect. Acute stressors can markedly enhance the release of corticotropin-releasing factor (CRF), and CRF injection into the nucleus accumbens increases the PIT effect. However, it is unknown whether acute stressors by themselves would amplify the PIT effect. Here, we examined the effects of acute stressors on PIT. Rats first received Pavlovian and instrumental training, and then the impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 57 publications
(58 reference statements)
3
12
1
Order By: Relevance
“…Results indicated that single exposure of the same multiple stressor as used in the current study reduced the overall lever press rate, but left intact the ability of a reward-predictive stimulus to invigorate instrumental responding, thereby suggesting that the acute stressor did not impair the retrieval of stimulus-reward associations (Pielock et al 2013). Our present results point to the possibility that twofold instead of single multiple stressor exposure could impair this type of stimulus modulation of instrumental performance.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…Results indicated that single exposure of the same multiple stressor as used in the current study reduced the overall lever press rate, but left intact the ability of a reward-predictive stimulus to invigorate instrumental responding, thereby suggesting that the acute stressor did not impair the retrieval of stimulus-reward associations (Pielock et al 2013). Our present results point to the possibility that twofold instead of single multiple stressor exposure could impair this type of stimulus modulation of instrumental performance.…”
Section: Discussionmentioning
confidence: 55%
“…For instance, male rats exposed to a predator, such as a cat, or to a female receptive rat showed equivalent increases in plasma corticosterone levels, but only cat-exposed rats exhibited working memory deficits (Woodson et al 2003). Together, these findings provide further evidence to the notion that plasma corticosterone levels are not always a sensitive index for stressor-induced behavioral effects (e.g., Natelson et al 1987;Pielock et al 2013).…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations